Thiocyanate ion-selective PVC membrane electrode [Articol] - Revenco, Mihail; Martin, Mariana; Dayyih, Waell Abu (Institute of Chemistry of ASM, 2010)
A potentiometric selective sensor based on trinuclear chromium(III) complex as a novel ionophore for the thiocyanate-selective electrode is reported. The sensor displays a near Nernstian slope of 57 ± 2 mV per decade, over a wide pH range 3 - 11. The working concentration range of the electrode is 1.10-5 – 1.10-1 mol/L with a detection limit of 5.10-6 mol/L. The sensor has a response time of 20 s and can be used for at least 6 months without any considerable fluctuation of the potential. The selectivity coefficients determined at using the fixed interference method indicate a good discriminating ability towards other anions. The prepared sensor was applied as an indicator electrode in the titration of thiocyanate with Ag+.
Keywords: thiocyanate; potentiometric sensor; titration